2022
DOI: 10.1029/2021tc007120
|View full text |Cite
|
Sign up to set email alerts
|

Active Back‐Arc Thrust in North West Java, Indonesia

Abstract: The Java Back‐arc Thrust scars the entire back‐arc area of Java Island, but the faults' nature, timing, and activity remain partly elusive. Characterizing the structure and activity of the seismogenic Java Back‐arc Thrust (historical earthquakes up to 7 Mw) is a cornerstone to evaluate associated geohazards. We focus on the western part of Java Back‐arc Thrust that reaches the megalopolis of Jakarta. We combine morphotectonic data, seismic reflection, electric resistivity profiles, kinematic, structural field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
1
13
0
2
Order By: Relevance
“…The results showed that the highest seismicity rates are found in the northern regions of West Java and Banten (corresponding to the highest a-value of 8.55) and the relatively high-stress tectonic regimes in the northern areas of Central Java and East Java (corresponding to the lowest b-value of 0.8). The high seismicity rate in the West Java northern side is supported by [68]. The high-stress tectonic regimes in the north of Central Java and East Java were in line with the results of time-domain moment tensor (TDMT) solutions, giving magnitudes of Mw 6.7 and Mw 7.0 with a resulting major double-couple component for the normal faulting types found for the events in examination, consistent with USGS.…”
Section: Projects Towards Vulnerability and Disaster Mitigation Studysupporting
confidence: 82%
“…The results showed that the highest seismicity rates are found in the northern regions of West Java and Banten (corresponding to the highest a-value of 8.55) and the relatively high-stress tectonic regimes in the northern areas of Central Java and East Java (corresponding to the lowest b-value of 0.8). The high seismicity rate in the West Java northern side is supported by [68]. The high-stress tectonic regimes in the north of Central Java and East Java were in line with the results of time-domain moment tensor (TDMT) solutions, giving magnitudes of Mw 6.7 and Mw 7.0 with a resulting major double-couple component for the normal faulting types found for the events in examination, consistent with USGS.…”
Section: Projects Towards Vulnerability and Disaster Mitigation Studysupporting
confidence: 82%
“… 2017 ), geological (Simandjuntak & Barber 1996 ; Aribowo et al . 2022 ) and seismological (Damanik et al . 2021 ; Widiyantoro et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Baribis Fault, a backarc thrust fault in West Java, has been active since the Pliocene but is less clearly expressed in its western extent, near Jakarta, than it is farther east (Aribowo et al . 2022 ). Subsequently, Widiyantoro et al .…”
Section: Introductionmentioning
confidence: 99%
“…Current subduction in the south of Java Island is almost trench-perpendicular with a convergence rate from 58 to 65 mm/year from west to east [23]. The neotectonic process generates earthquakes in the subduction megathrust and onshore faults, and most of them rupture in the relatively W-E direction, such as the the Cimandiri [8,24], Lembang [25,26], and Baribis Faults [27,28] in the western part of Java island. Several other seismic activity clusters have been reported with a relative NE-SW direction in the southern part of Java Island in recent years, one of which is the Garsela Fault [29].…”
Section: Geological Settingmentioning
confidence: 99%